Menopause and the Social Determinants of Health - Heather Quaile; Sameena Rahman; Kudzai Dombo; Louise Newson; Sara Perelmuter (Obstetrics & Gynecology, 2026)
This clinical perspective examines how social determinants of health (SDoH) such as economic stability, education and health literacy, health care access and quality, and social and community contexts shape menopause experiences and outcomes through a health equity lens. Menopause is not experienced uniformly: Black, immigrant, and LGBTQ+ (lesbian, gay, bisexual, transgender, queer+) individuals and those with low income often face earlier symptom onset, greater symptom burden, and reduced access to evidence-based care due to structural inequities, economic barriers, and cultural stigma. Menopause care must move beyond a purely biological model to incorporate the social, economic, and cultural realities that influence symptom recognition, treatment access, and long-term health. Integrating SDoH screening, expanding inclusive research, and advancing culturally responsive, trauma-informed, person-centered care are essential to improving menopause outcomes and promoting equitable healthy aging.